A novel risk score (MCCT) to guide decision for treatment of advanced hepatocellular carcinoma with transarterial chemoembolisation: a derivation and validation study. (October 2016) - Zhang, Yong-Fa; Shi, Ming; Guo, Rong-Ping
Abstract: Background: Transarterial chemoembolisation (TACE) is still widely used to treat patients with advanced hepatocellular carcinoma who have no access to sorafenib in Asia. However, the indication of TACE for these patients has yet to be established. We established an objective point score to guide this decision in patients with advanced-stage hepatocellular carcinoma. Methods: We developed a scoring system (MCCT score) based on preoperative data from a cohort of 422 patients receiving TACE as the first treatment for advanced hepatocellular carcinoma from 2006 to 2013 at Sun Yat-sen University Cancer Center, Guangzhou, China. Factors determining survival were analysed by univariate and multivariate analysis and Cox proportional hazard regression models. The scoring system was retrospectively validated in an external cohort from other two institutions (Dongguan People's Hospital and the Kaiping Central Hospital; n=237). The prognostic predictive power was compared with six different staging systems: tumour node metastasis (TNM), 7th edition; Cancer of the Liver Italian Program (CLIP); Chinese University Prognostic Index (CUPI); Okuda, Japan Integrated Staging (JIS); and Groupe d'Etude et de Traitement du Carcinome Hépatocellulaire (GRETCH). The retrospective study was approved by the institutional review board; written informed consent was obtained from each patient. Findings: The presence of macroscopic vascular invasion (M), Child-Pugh class B (C), C-reactive protein values (C) higher than 10 mg/L, and tumour size (T) larger than 7 cm were independent negative prognostic factors for survival and were used to create the MCCT score. The patients were divided into risk groups on the basis of their MCCT scores (low risk for ≤2 points, intermediate risk for 3–4 points, and high risk for five points). The median overall survival times were 14·4 months (95% CI 10·7–18·1) for the low-risk group, 6·8 months (6·0–7·6) of the intermediate-risk group, and 3·2 months (1·7–4·7) for the high-risk group (p<0·0001). The discriminative ability, as determined by the area under the curve (AUC) at 6 and 12 months (AUCs 0·692 at 6 months and 0·702 at 12 months) seemed to be greater than the ability of the six other hepatocellular carcinoma staging systems (AUCs range 0·501 to 0·633). The findings were supported by the external validation cohort. Interpretation: The MCCT scoring system is more accurate than the six other scoring systems in selecting patients with advanced hepatocellular carcinoma for TACE. For patients with advanced hepatocellular carcinoma with no access to sorafenib, TACE may be a valuable alternative in selecting patients (MCCT score ≤2). Funding: This study was supported by grants from theNational Natural Science Foundation of China (81172037/H1606, 81272639, and 81572385 ), Guangdong province science and technology project of China (2013B021800159 ), and theFundamental Research Funds for the Central Universities of China (13ykzd24 ).